A partial pterosaur ulna from the Candeleros Formation (Neuquén Group), Late Cretaceous of Argentina - Haluza, Alejandro (2013)
The proximal portion of the left ulna of a pterosaur is described. The specimen comes from the Candeleros Formation (Cenomanian), Neuquén Group, at Cabo Alarcón, Neuquén province, Argentina. The analysis of this new specimen allows the re-interpretation of a previously described pterosaur tibia founded at Los Catutos locality, Neuquén (MOZ 2280 P) as a proximal ulna. The new material belongs to a medium-sized pterosaur, considerably larger than previously recorded pterosaurs from this geological unit. The analysis of correlation between ulnar length-pes length in well-known pterodactyloid pterosaurs shows that the new ulna matches well with the inferred size of the Pteraichnus isp. trackmaker recorded from the same formation.